Catalytic Stability Study of a Pd‐Ni2P/C Catalyst for Formic Acid Electrooxidation. Issue 5 (8th March 2017) - Wang, Shuli; Chang, Jinfa; Xue, Huaiguo; Xing, Wei; Feng, Ligang
Abstract: In this work, the catalytic stability of Pd‐Ni2 P/C, a highly efficient anode catalyst for direct formic acid fuel cells, was studied by using electrochemical and physical techniques. The dynamic stability was probed in an accelerated stability test (AST) by using cyclic voltammetry for 1000 cycles, and a very low performance decay rate was observed on the Pd‐Ni2 P/C catalyst compared with a homemade Pd/C catalyst. About 60 % of the initial peak current density, three times higher than that of the homemade Pd/C catalyst, was retained after the AST on the Pd‐Ni2 P/C catalyst. There were no obvious structure and morphology changes in the Pd‐Ni2 P/C catalyst revealed by X‐ray diffraction, X‐ray photoelectron spectroscopy, or transmission electron microscopy characterization. However, largely increased Pd particle sizes that appear on the Pd/C catalyst might lead to serious performance decay. The strong interaction of Pd and Ni2 P in the catalyst system might increase the anchoring of Pd nanoparticles on the support surface, thus less Pd was lost during electrocatalysis. Steady‐state stability tests further confirmed the high stability of the Pd‐Ni2 P/C catalyst, and the high anti‐poisoning ability to CO‐like intermediates would maintain the high stability. The results are important for an in‐depth understanding of the contribution of Ni2 P in the catalyst system. Abstract : Up for promotion : The catalytic stability of a novel highly efficient Pd‐Ni2 P/C catalyst for formic acid oxidation is probed by using physical and electrochemical techniques. The result is beneficial to understand the role of a catalytic promoter, like phosphide, in the catalyst system for fuel cell catalysis.